Kajian Literasi Statistik pada Jenjang Pendidikan di Indonesia - Ema Butsi Prihastari; Sukestiyarno Sukestiyarno; Kartono Kartono (Universitas Mathla'ul Anwar Banten, 2022)
This study aims to describe the definition of statistical literacy carried out in mathematics learning and its indicators by reviewing and analyzing the results of related research conducted from 2012 to 2022 in Google Scholar using publish or perish software. The method used is a literature review by selecting articles that have been published and in accordance with keywords. There were 11 articles published in relevant national and SINTA journals. The results of the research found can answer research questions, as follows: (a) the definition of statistical literacy is the ability used by a person by using statistical procedures on qualitative and quantitative data which begins with understanding data, processing data, presenting data, interpreting data, and making conclusions used to solve daily problems. And statistical literacy indicators are obtained, namely,1) reading to understand the data, 2) analyzing the data, 3) presenting the data, 4) interpreting the data, and 5) concluding or presenting the data. Research on statistical literacy variables is mostly carried out in universities with qualitative research types